Coxsackievirus B3 sequences in the myocardium of fatal cases in a cluster of acute myocarditis in Greece. Issue 4 (24th March 2005) - Spanakis, N; Manolis, E N; Tsakris, A; Tsiodras, S; Panagiotopoulos, T; Saroglou, G; Legakis, N J
Abstract : Aim: The investigation of three fatal cases during a nationwide cluster of cases of an upper respiratory tract infection (URTI) associated with myocarditis and/or pericarditis in Greece in 2002. Methods: In the three women who died, necropsies were performed and tissue sections were taken for histological examination, antigen detection by immunohistochemistry and indirect immunofluorescence assay (IFA), amplification of viral genomes by nested reverse transcription polymerase chain reaction (RT-PCR), and sequence analysis. Results: All samples showed histological signs of active myocarditis. Immunohistochemistry revealed the presence of the enterovirus VP1 family of proteins and IFA revealed the presence of coxsackievirus B3 antigen. Nested RT-PCR amplified enteroviral alleles of the 5′-untranslated region which were identical to each other and to the coxsackievirus B3 sequences. Conclusions: This study provides pathological evidence of enteroviral infection among fatal myocarditis cases in a nationwide URTI cluster of cases associated with myocarditis and/or pericarditis.